The The Paradoxes of the Modern Geistes: Critico-Comparative Introspect of the Previous Century - Servaña, Alvin (Philosophy and Realistic Reflection, 2026)
This essay investigates the existential and philosophical dilemmas of modernity, drawing on the prophetic insights of Friedrich Nietzsche and José Rizal as critical entry points. Though situated on opposite ends of the globe, both thinkers discerned a paradox at the heart of modernity: its promise of liberation entwined with new forms of domination. Nietzsche’s pronouncement of the “death of God” diagnosed the spiritual vacuum of Western civilisation, while Rizal’s critique of colonial modernity exposed the violence embedded in imperial progress. Together, they illuminate the dialectics between emancipation and barbarism that have shaped the past century. Complementary reflections by Paul Johnson, Viktor Frankl, and Aleksandr Solzhenitsyn highlight modernity’s contradictions, particularly the instrumental rationality that enabled both human flourishing and systematic destruction. Cultural transformations, marked by the fragmentation of coherent narratives, are further exemplified in the literary visions of W. Somerset Maugham and Gabriel García Márquez, whose works capture the dissonance of fractured modern identities. The inquiry culminates in an exploration of hypermodernity’s crisis of selfhood, where digital “excarnation” threatens embodied human experience. Against this backdrop, the essay advocates for situated transcendence and moral imagination as pathways to reclaim sensibility amid disintegration. By echoing the voices of past thinkers, it calls for a conscious inhabiting of modernity’s tensions—an effort to confront paradoxes with compassion and creativity. Ultimately, the essay envisions more grounded in ethical vigilance and imaginative renewal, as antidotes to the alienation of the contemporary age. Echoing the voices of past thinkers, it calls for a nuanced engagement with the unresolved paradoxes of the modern Geistes—an effort to inhabit its tensions consciously and compassionately while envisioning more humanistic futures.